Reforming Indonesian Rape Law: Adopting U.S. Rape Shield Law in Excluding Prejudicial Evidence - Ramadhan, Choky R. (UI Scholars Hub, 2018)
Rape is a complicated crime in term of law enforcement. It is usually occurred by someone who has close relationship or connection to the victim. The availability of evidence is also limited. Unfortunately, sexual violence victim often does not receive proper handling from law enforcement. In several cases, the judge undermined victim’s testimony because of past sexual history and lack of resistance that led to more lenient punishment or acquit the defendant. Therefore, I assert that rape law itself should be revised to minimize judge’s prejudice or bias to several shreds of evidence. I suggest that Indonesia could learn from U.S. rape shield law that gives more protection to sexual violence victim. This law encourages the victim to report and increases the probability of conviction because it excludes victim’s previous sexual history and lack of resistance.